2020
DOI: 10.1016/j.foodchem.2020.127197
|View full text |Cite
|
Sign up to set email alerts
|

Scientific basis for the industrialization of traditionally used plants of the Rosaceae family

Abstract: Plants have been traditionally used for the treatment of different types of illness, due to biomolecules with recognised benefits. Rosaceae family is used in traditional Galician medicine. The following plants Agrimonia eupatoria, Crataegus monogyna, Filipendula ulmaria, Geum urbanum, Potentilla erecta and Rosa canina are usually found in treatments. The aim of this study is to perform an ethnobotanical review about the bioactive compounds of these plants and their different bioactivities, both studied in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 84 publications
(153 reference statements)
0
28
0
2
Order By: Relevance
“…All the aforementioned conditions, together with biochemical traits, may affect the quantitative variation of pigments in rose fruits [3,7] because of their effects on carotenoids biosynthesis. Taking into account the various growing locations of the rosehips collected, it could be assumed that the different abiotic factors influenced carotenoids biosynthesis in most of the cultivated rosehips (7, and 8, 10 HC) as well as in wild rosehips (3,4,5,6 HW), compared to all other locations (indicated by the positive loading of PC1 and PC2). According to the literature, no differences in β-carotene content were observed between some wild and cultivated rosehip [56].…”
Section: Principal Component Analysis Of the Data Obtained From Raman Spectra Of Rosehip Hypanthium Parenchyma Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the aforementioned conditions, together with biochemical traits, may affect the quantitative variation of pigments in rose fruits [3,7] because of their effects on carotenoids biosynthesis. Taking into account the various growing locations of the rosehips collected, it could be assumed that the different abiotic factors influenced carotenoids biosynthesis in most of the cultivated rosehips (7, and 8, 10 HC) as well as in wild rosehips (3,4,5,6 HW), compared to all other locations (indicated by the positive loading of PC1 and PC2). According to the literature, no differences in β-carotene content were observed between some wild and cultivated rosehip [56].…”
Section: Principal Component Analysis Of the Data Obtained From Raman Spectra Of Rosehip Hypanthium Parenchyma Cellsmentioning
confidence: 99%
“…The rosehip of this species has many beneficial effects, such as anti-diarrhoeic, astringent, healing, depurative, diuretic and venotonic, and it is mainly used as infused, tinctured or consumed as syrup or dragees. On the other hand, the seeds are a rich source of polyunsaturated fatty acids and were used in folk medicine in wound-healing and skin disease treatments [4]. Rosehips and/or petals can be used in gastronomy (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ever-growing interest in the search of new therapeutic compounds against cancer has pushed researchers to look for innovative sources of anticancer compounds in natural sources, including plants [31]. Traditionally, plants have been used in all cultures for healing diverse diseases and improve well-being [32,33]. Further research demonstrated that traditional-used plants contain bioactive compounds, which administered in sufficient doses, have positive effects on health.…”
Section: Introductionmentioning
confidence: 99%
“…Most of extracts from the plant material are good sources of phenolic compounds and utilized for healing pathological problems (Alcântara et al, 2019;Garcia-Oliveira et al, 2020;García-Cruz et al, 2017). Consumption of plant materials such as fruits and vegetables contribute to the prevention of many ailments owing to the presence of some phenolics in the plant materials (Septembre-Malaterre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%